Empreendedorismo e equidade de gênero: um olhar crítico sobre as práticas de mediação de informação no contexto materno - Cananéa, Lílian Viana Teixeira (2023)
The research has as its central theme the process of mediation, appropriation and use of information delimited by the following question: how do information mediation practices in the area of maternal entrepreneurship influence the construction of the social world view of individuals, especially women-mothers? We argue that the information mediation practices of maternal entrepreneurs reveal the patriarchal view of being a woman and mother, which includes the formation of the perfect woman, wonder woman and warrior, who handles all her activities in an exemplary, everyday way (woman , mother, wife, housewife, professional, etc) and excessively positive, thus being solely responsible for their own success or failure in life and career. In this sense, we analyze how the information mediation practices of the founders of EME reinforce and maintain elements of reproduction of male domination. Of a qualitative nature, with regard to the reality approach, and documental as to the sources of information used, we opted for the case study of the school of entrepreneurship, whose proposal is to help women-mothers to invest in their own business and, thus, to be protagonists of your own choices. Data analysis/interpretation was performed using Content Analysis, in the light of Bourdieu's Praxiology. The results found corroborate the constructed hypothesis that, although the school's proposal has an emancipatory and activist character, the informational practices mediated by its administrators reinforce the male habitus, by stimulating and naturalizing the image of the successful super-mother. The effort and interest in looking at this object was to perceive how, even where there was supposed to be a sigh of emancipation and transformation, there are also captures and twists that overshadow the look on power relations. Finally, we conclude that there is an urgent need for more solid public policies in favor of these women, especially in the corporate environment that still has as a professional practice the exclusion of mothers and male enhancement, with opportunities that do not take into account the specific characteristics of these two publics.